Revolutionizing Courier Services: The Holistic Impact of Digital Marketing Strategies on Fast Delivery in Nigeria - Ajayi Olalekan Ezekiel; Adeyeye Charles Tolulope; Salau Alhaji Abdulazeez; Kamoru Lanre Akanbi; Philips Olugbenga; Adebayo (PT FORMOSA CENDEKIA GLOBAL, 2024)
The study examines the holistic impact of digital marketing strategies on fast delivery in Nigeria. A descriptive survey research design was utilized and a sample size of one hundred and forty-four was used. Data was analyzed using descriptive and inferential statistics with the help of the IBM-SPSS version 27. The result found that content marketing significantly and independently predicts fast courier services (β = .61, t = 9.12, p<.05). The result also found that search engine optimization significantly and independently predicts fast courier services (β = .48, t = 6.58, p<.05). The result also found that email marketing significantly and independently predicts fast courier services (β = .17, t = 2.09, p<.05). Finally, there was significant joint prediction of content marketing, search engine optimization and email marketing on job performance F (3,140) = 32.44, R2 = 0.41; p<.05). These results demonstrate how technological advancements and digital marketing has potentially and completely transform courier services and fast delivery of courier services in Nigeria, providing numerous chances for companies to improve their delivery capacities and clientele. In the context of fast delivery services of courier service in Nigeria, the paper work out the impact of new technology on the transformative potential of digital marketing strategies through the technological innovations